High sensitivity and multicolor tunable optical thermometry in Bi3+/Eu3+ co-doped Ca2Sb2O7 phosphors. (January 2023) - Shi, Xinyang; Zhang, Muhua; Lu, Xinyue; Mao, Qinan; Pei, Lang; Yu, Hua; Zhang, Jian; Liu, Meijiao; Zhong, Jiasong
Abstract: Currently, with increasing demand for non-contact fluorescence intensity ratio-based optical thermometry, a novel phosphor with high-efficiency, dual-emitting centers, and differentiable temperature sensitivity is more and more urgent to develop. In this work, an efficient dual-emitting center optical thermometry with high sensitivity and multicolor tunable in Ca2 Sb2 O7 :Bi 3+, Eu 3+ phosphor is firstly designed and successfully prepared. Under 330 nm excitation, the fabricated phosphor presents the featured and distinguishable emissions of Bi 3+ and Eu 3+ ions. The high efficiency energy transfer from Bi 3+ to Eu 3+ ions is proved and its corresponding mechanism belongs to dipole-dipole interaction. By modulating the ratio of Bi 3+ /Eu 3+, the multicolor changes from blue to pink are realized. Based on the discriminative thermal quenching behavior between Bi 3+ and Eu 3+, the fluorescence intensity ratio of Eu 3+ to Bi 3+ in Ca2 Sb2 O7 samples illustrates excellent optical thermometry performance from 298 to 523 K. The maximum absolute sensitivity ( S a ) and relative sensitivity ( S r ) reach as high as 0.2773 K −1 at 523 K and 2.37% K −1 at 448 K, respectively. Notably, the discriminated surrounding temperature can be directly confirmed by observing the emitting color from purple to orange-red with the temperature increase from 298 to 523 K. Furthermore, the as-prepared phosphor materials also demonstrate outstanding repeatability and excellent reversibility. These results exhibit that the designed Ca2 Sb2 O7 :Bi 3+, Eu 3+ phosphors have great promising applications in the field of non-contact optical temperature thermometry and thermochromic. Graphical abstract: Image 1 Highlights: The multicolor visible emissions are realized by modifying the ratio of Bi 3+ /Eu 3+ . The maximum S a and S r reach as high as 0.2773 K −1 at 523 K and 2.37% K −1 at 448 K. The discriminated surrounding temperature can be directly confirmed by observing the emitting color. The fabricated materials demonstrate outstanding repeatability and excellent reversibility.